2000
DOI: 10.1002/(sici)1097-4652(200002)182:2<281::aid-jcp17>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for intracellular cleavage of plasminogen activator inhibitor type 2 (PAI-2) in normal epidermal keratinocytes

Abstract: Plasminogen activator inhibitor type 2 (PAI-2) is a serine proteinase inhibitor (serpin), present in high quantities in stratified squamous epithelia. Detergent extracts of human epidermis or cultured keratinocytes contain primarily active, nonglycosylated PAI-2. In keratinocytes, the vast majority of PAI-2 is retained within the cell, supporting the hypothesis that PAI-2 may serve specific intracellular function(s) through interaction with an unknown cytoplasmic proteinase. During interaction with the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
22
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 37 publications
6
22
0
Order By: Relevance
“…There is no direct evidence to show that PAI-2 inhibits uPA in vivo, and several studies on the physiological role of PAI-2 have inferred a uPA-independent intracellular function for PAI-2 (13,26,39,49,51,55). The proposed new Rb-associated activity for PAI-2 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no direct evidence to show that PAI-2 inhibits uPA in vivo, and several studies on the physiological role of PAI-2 have inferred a uPA-independent intracellular function for PAI-2 (13,26,39,49,51,55). The proposed new Rb-associated activity for PAI-2 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PAI-2 contains a unique C-D interhelical region, which is larger than any identified to date in the ov-serpin family (12,45). A growing number of studies (2,6,11,12,26,39,40,44,45,49,54,55) have suggested that PAI-2, like other ov-serpins (45), may have an intracellular function distinct from its extracellular role as a uPA inhibitor, since the consequences of PAI-2 expression are often difficult to associate with uPA inhibition. PAI-2 expression by cancer cells has been associated repeatedly with a lower incidence of metastases and an improved prognosis (17,34,37,53), whereas expression of PAI-1, also an effective inhibitor of uPA, largely fails to correlate with an improved prognosis.…”
mentioning
confidence: 99%
“…Primary cornea and conjunctiva cell cultures were initiated from the biopsies as previously described by Williams et al, 5 and Risse-Marsh et al 6 Cells between the first and sixth passages were used for the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] Extracellular PAI-2 is a potent inhibitor of urokinase-type plasminogen activator (u-PA) and, although the intracellular targets and the molecular mechanism of PAI-2 remain undefined, different studies have indicated that PAI-2 acts as a multifunctional protein, since, it is involved in the regulation of fibrinolysis, in the regulation of keratinocytes development, in proliferation, in the invasion and metastasis of cancer cells, and in conferring resistance to apoptosis. [6][7][8] It has been reported that PAI-2 is constitutively expressed in human stratified squamous epithelia and suggested that this inhibitor could be involved in the differentiation or in the antimicrobial defense mechanisms of at least some epithelia. 5 For instance, it has been reported that PAI-2 could be a product of differentiating corneal keratinocytes, since in human corneal epithelium PAI-2 is present exclusively in the most superficial cell layers (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed at high levels in the skin, hair follicles, gingival cells, the cervix, and placenta. PAI-2 is crosslinked to create the cornified envelope in terminally differentiated epithelial cells, where it forms a proteinaceous coat, with PAI-2 in both the active and relaxed forms (11,12).PAI-2 appears to have several distinct biological functions (10). To date, complexes between PAI-2 and uPA have not been observed in vivo.…”
mentioning
confidence: 99%